2021
DOI: 10.3389/fendo.2021.740200
|View full text |Cite
|
Sign up to set email alerts
|

Causal Associations of Obesity With the Intervertebral Degeneration, Low Back Pain, and Sciatica: A Two-Sample Mendelian Randomization Study

Abstract: The role of obesity in the development of dorsopathies is still unclear. In this study, we assessed the associations between body mass index (BMI) and several dorsopathies including intervertebral disc degeneration (IVDD), low back pain (LBP), and sciatica by using the Mendelian randomization method. We also assessed the effect of several obesity-related traits on the same outcomes. Single-nucleotide polymorphisms associated with the exposures are extracted from summary-level datasets of previously published g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
1
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 46 publications
5
25
1
2
Order By: Relevance
“…For the underlying disease group, we included the existing underlying diseases as influencing factors into the model for analysis and showed that age and BMI had the greatest impact on the degree of IVDD and facet joint degeneration, which is consistent with other studies (43)(44)(45)(46). Of note, we found that the proportion of each underlying disease is minor.…”
Section: Discussionsupporting
confidence: 86%
“…For the underlying disease group, we included the existing underlying diseases as influencing factors into the model for analysis and showed that age and BMI had the greatest impact on the degree of IVDD and facet joint degeneration, which is consistent with other studies (43)(44)(45)(46). Of note, we found that the proportion of each underlying disease is minor.…”
Section: Discussionsupporting
confidence: 86%
“…These include BMI and the general perception of one’s own health, followed by the extent of pre-existing diseases and medications as a measure of the actual pre-existing medical conditions. This confirms on the one hand known associations with the development of neuropathic pain, such as the influence of BMI [ 21 , 22 ], but on the other hand also reveals new aspects that need to be investigated in more detail in the further course of this study.…”
Section: Discussionsupporting
confidence: 82%
“…LBP has become a common disease that affects the physical and mental health of elderly people, causing a great economic burden on society [ 27 , 28 ]. IVDD is a primary cause of LBP [ 29 ].…”
Section: Discussionmentioning
confidence: 99%